Flowering control of Citrus with bioregulators and stressors - Hiller Hernandez, Johann (2024)
Citrus fruits and their industry represent an important part of Brazilian agriculture. To ensure enough yields, it is crucial to have enough flowering to ensure successful fructification and productivity. The physiological mechanisms surrounding the flowering of this genus have been studied throughout the world, shedding light on the genes, hormones, and signals involved in successful flower induction. Treatments like girdling, water stress, and foliar application of chemical substances have been part of these investigation efforts aimed towards enhancing or decreasing flower intensity to the desire and need of the farmers. To understand the efficiency of these treatments in southeast Brazilian conditions, a study was carried out using 9 different of them and a control, with 6 plants for each, including physical and chemical practices. These had a combination or sole use of girdling, water stress, AVG (aminoethoxyvinylglycine), ethephon (2-chloroethylphosphonic acid), urea, gibberellic acid, 2,4-D (2,4-diclorophenoxy acetic acid), and a commercial biostimulant with single dosages. The plant material used was 60 two-year-old Valência Americana sweet orange trees, planted in 20 L vases in an open air meshed greenhouse at the ESALQ-USP Campus in Piracicaba, Brazil. The data obtained were submitted for analysis of variance (ANOVA) using Tukey\'s range test at 5% significance using the SPEED Stat spreadsheet. No significant difference in the total flower number was found between the control and the treatments, yet some significant differences between the treatments were observed. The girdled plants flowered intensely before all other treatments. The reproductive shoots were mostly multiflowered in most treatments and the control. The water stress + gibberellic acid treatment strongly inhibited flowering. Some girdled treatments showed significantly less vegetative development in the parameters of fresh treetop weight, SPAD index, stem thickness growth speed, and root weight. No significant difference was found regarding the vegetative growth speed.